CODE, CURE, REPEAT: AI REDEFINING ANTIBIOTIC TREATMENT (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
In 1928, Alexander Fleming returned to his laboratory at St. Mary’s Hospital to find a mold-contaminated petri dish that would forever change medicine. That serendipitous moment—penicillin’s discovery—ushered in the antibiotic era, transforming once-fatal bacterial infections into manageable ailments. For decades, the pharmaceutical industry relied on a similar playbook: soil screening, natural product extraction, and semi-synthetic modifications. Yet this golden age has long since faded. The pipeline of new antibiotics has dried to a trickle, while pathogenic bacteria have evolved into multidrug-resistant superbugs that render our existing arsenal increasingly obsolete .Today, humanity faces a paradox. We possess more biomedical knowledge than ever before, yet we are losing the arms race against microbes. The World Health Organization now warns that antimicrobial resistance (AMR) is outpacing advances in modern medicine, with one in six laboratory-confirmed bacterial infections worldwide resistant to antibiotic treatments as of 2023 . Between 2018 and 2023, resistance rose in over 40% of pathogen-antibiotic combinations monitored globally, climbing at an average annual rate of 5–15% . In this bleak landscape, a new protagonist has emerged—not from a petri dish, but from lines of code.